Raised IL-2 and TNF-α concentrations are associated with postoperative delirium in patients undergoing coronary-artery bypass graft surgery. (17th December 2013) - Kazmierski, Jakub; Banys, Andrzej; Latek, Joanna; Bourke, Julius; Jaszewski, Ryszard
ABSTRACT: Background: The knowledge base regarding the pathogenesis of postoperative delirium is limited. The primary aim of this study is to investigate whether increased levels of IL-2 and TNF-α are associated with delirium in patients who underwent coronary-artery bypass graft (CABG) surgery with cardiopulmonary bypass (CPB). The secondary aim is to establish whether any association between raised cytokine levels and delirium is related to surgical and anesthetic procedures or mediated by pre-existing conditions associated with raised cytokine levels, such as major depressive disorder (MDD), cognitive impairment, or aging. Methods: Patients were examined and screened for MDD and cognitive impairment one day preoperatively, using the Mini International Neuropsychiatric Interview and The Montreal Cognitive Assessment and Trail Making Test Part B. Blood samples were collected postoperatively for cytokine levels. Results: Postoperative delirium screening was found positive in 36% (41 of 113) of patients. A multivariate logistic regression revealed that an increased concentration of pro-inflammatory cytokines is associated with delirium, and related to advancing age, preoperative cognitive decline of participants, and duration of CPB. According to receiver operating characteristic analysis, the most optimal cut-off for IL-2 and TNF-α concentrations in predicting the development of delirium were 907.5 U/ml and 10.95 pg/ml, respectively. Conclusions: The present study suggests that raised postoperative cytokine concentrations are associated with delirium after CABG surgery. Postoperative monitoring of pro-inflammatory markers combined with regular surveillance may be helpful in the early detection of postoperative delirium in this patient group.